2016
DOI: 10.1002/mabi.201500353
|View full text |Cite
|
Sign up to set email alerts
|

A Selective Mucin/Methylcellulose Hybrid Gel with Tailored Mechanical Properties

Abstract: Mucin glycoproteins are key components of native mucus which serves as an initial barrier in the human body against microbial attack. Mucins are able to prevent bacterial adhesion and can trap viruses. However, the weak mechanical properties of mucin solutions have so far prevented their application in a physiological environment. Here, methylcellulose biopolymers are used as mechanical adjuvants to overcome this limitation and generate a thermoresponsive mucin/methylcellulose hybrid system. The hybrid materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…In the central part of the molecule, the mucin glycoprotein comprises densely glycosylated regions, and several carbohydrates found in this region (such as sialic acid or sulfated sugar residues) possess a strongly anionic character. [31] Consistently, mucins have been previously reported to bind cationic particles and molecules, [32][33][34][35][36] and we expect that a mucin coating will allow our filter to selectively remove cationic particles or molecules by electrostatic forces.…”
Section: Resultssupporting
confidence: 76%
“…In the central part of the molecule, the mucin glycoprotein comprises densely glycosylated regions, and several carbohydrates found in this region (such as sialic acid or sulfated sugar residues) possess a strongly anionic character. [31] Consistently, mucins have been previously reported to bind cationic particles and molecules, [32][33][34][35][36] and we expect that a mucin coating will allow our filter to selectively remove cationic particles or molecules by electrostatic forces.…”
Section: Resultssupporting
confidence: 76%
“…The hydrophilicity and negative charge of mucins were also used by Nowald et al who mixed pig gastric mucins with methylcellulose to create thermo-sensitive selfstanding hydrogels that bound to positively charged molecules. 93 By removing some of the pig gastric mucin glycosylation, Fukui et al were able to generate nanoparticles that could incorporate positively charged antibacterial lysozyme enzymes. 94 The particles degraded over time and released their content, due to the proteolytic action of the encapsulated lysozyme.…”
Section: Exploiting the Complex Chemistry Of Mucinsmentioning
confidence: 99%
“…[3][4][5] Therein, MC acts as an emulsifier, viscosity controller, and mechanical adjuvant for composite systems. [6] It has been shown that 2.49 wt% of MC having molecular weight of 310 kDa and a degree of substitution of 1.8 display lower critical solution temperature (LCST) at 29 ± 2 o C, below which Newtonian flow is observed and above which non-Newtonian flow and increased viscosity emerge. [7] The aqueous dispersions exhibit thermosensitive hydrogelation.…”
Section: Introductionmentioning
confidence: 99%